(untitled) (Horizontes de Enfermería, 2020)
The determinants of health are distributed within a social gradient, in which the more the social ladder descends, the living conditions decrease, and therefore the prevalence of disease increases. (Marmot, 2012. Thus it is necessary to analyze in detail the determinants that can influence the nutritional status measured through the BMI. The type of study is a cross-sectional descriptive. The objective is: to establish the relationship of the social determinants on the nutritional status of those in young adults of the Chical, Maldonado, and Tobar Donoso parishes of the Tulcán canton. The results obtained were that gender is not a statistically significant variable given in similar amounts; in the occupation, there is a greater prevalence of altered nutritional status in housewives with 27%, the variable level of education is directly related to an altered nutritional status 30% of the population with primary education, the variable economic income is evidence of a 39% prevalence of altered nutritional status. Conclusions: The alteration of the nutritional status is related to the social determinants of health such as education, occupation, and economic income that emerge from the inequities and inequalities of these vulnerable sectors.